Humanized Anti-CD19 CAR-T Cell Therapy and Sequential Allogeneic Hematopoietic Stem Cell Transplantation Achieved Long-Term Survival in Refractory and Relapsed B Lymphocytic Leukemia: A Retrospective Study of CAR-T Cell Therapy - Chen, Wei; Ma, Yuhan; Shen, Ziyuan; Chen, Huimin; Ma, Ruixue; Yan, Dongmei; Shi, Ming; Wang, Xiangmin; Song, Xuguang; Sun, Cai; Cao, Jiang; Cheng, Hai; et al. (Frontiers in Immunology, 2021)
Early response could be obtained in most of patents with relapsed or refractory B cell lymphoblastic leukemia (R/R B-ALL) treated with Chimeric Antigen Receptor T-Cell (CAR-T) therapy, but relapse occurs in some patients. There is no consensus on treatment strategy post CAR-T cell therapy. In this retrospective study of humanized CD19-targeted CAR-T cells (hCART19s) therapy for R/R B-ALL, we analyzed the patients treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT) or received a second hCART19s infusion, and summarized their efficacy and safety. We retrospectively studied 28 R/R B-ALL patients treated with hCART19s in the Affiliated Hospital of Xuzhou Medical University from 2016 to 2020. After the first hCART19s infusion, 10 patients received allo-HSCT (HSCT group), 7 patients received a second hCART19s infusion (CART2 group), and 11 patients did not receive HSCT or a second hCART19s infusion (CART1 group). The safety, efficacy, and the long-term survival were analyzed. Of 28 patients received hCART19s treatment, 1 patient could not be evaluated for efficacy, 25 (92.6%) achieved complete remission (CR) with 20 (74.7%) achieved minimal residual disease (MRD) negativity. Seven (25.9%) patients experienced grade 3-4 CRS, and 1 died from grade 5 CRS. No patient experienced ≥3 Grade ICANS. The incidence of second CR is higher in HSCT group compared to CART2 group (100% vs. 42.9%, p=0.015). The median follow-up time was 1240 days (range: 709-1770). Significantly longer overall survival (OS) and leukemia-free survival (LFS) were achieved in HSCT group (median OS and LFS: not reached, p=0.006 and 0.026 respectively) compared to CART2 group (median OS: 482; median LFS: 189) and CART1 group (median OS: 236; median LFS: 35). In the HSCT group, the incidence of acute graft-versus-host disease (aGVHD) was 30% (3/10) and transplantation related mortality (TRM) was 30% (3/10). No chronic GVHD occurred. Multivariate analysis results showed that blasts ≥ 20 % in the bone marrow and MRD ≥ 65.6% are independent factors for inferior OS and LFS, respectively, while receiving allo-HSCT is an independent factor associated with both longer OS and LFS. In conclusion, early allo-HSCT after CAR-T therapy can achieve long-term efficacy, and the adverse events are controllable.